Development and Characterization of Dual Cross-linked Microbeads for Colon Specific Targeting: Release Kinetic Modeling and Gamma Scintigraphy Studies - Lanjhiyana, Dr. S. K. (Asian Journal of Pharmaceutics (AJP), 2022)
Objective: The aim of present study is to develop and characterize ionic gelation-based dual Ca2 + and SO4 2- crosslinked gel microbeads using blend mixture of biodegradable chitosan and sodium alginate for colon targeting. Methods: Those diclofenac sodium (DS) loaded microbead formulations were prepared by utilizing ionic gelation based polyelectrolyte complexes technique that was effectively dual cross-linked with Ca2 + and SO4 2- ions containing solutions. Results: The result for surface morphology characterization through scanning electron microscopy revealed for semispherical and wrinkled shaped rough surfaces of those optimized formulations. The mean particle size of 761.52–895.22 μm, entrapment efficiency 63.45–78.38% of, and percentage yield of 73.28– 78.69% are resulted, respectively. The swelling degree of those optimized formulations is found with slighter values into acidic gastric medium (pH = 1.2), whereas increased values into alkaline intestinal mediums (pH = 6.8 and 7.4), respectively, during 4-h time intervals. The experimental vitro release studies revealed for negligible amount of DS that was released into simulated gastric fluid medium during 2 h, while slower drug released into simulated intestinal fluid medium during 3 h and augmented released into stem cell factor medium during 18 h studies, respectively. Furthermore, the drug release kinetics modeling studies performed for those optimized formulations revealed for non-fickian mechanism type that was best fitted with Higuchi and Korsemeyer peppas mathematical models. These confirmed that drug releases was guided by dual mechanisms of diffusion and erosion simultaneously. Conclusion: The developed experimental formulations may be used for targeting of DS into colon and possible management of inflammatory bowel disease, respectively.